Developing Students’ Multimodal Communicative Competence Through Multiliteracies Pedagogy - Prihantoro, Prihantoro; Suherdi, Didi; Muslim, Ahmad Bukhori (Institut Agama Islam Negeri (IAIN) Curup, 2022)
With the rise of globalization, digitization, and the emergence of the fourth industrial revolution, meaning-making modes are now increasingly multimodal in which written linguistics modes of meaning interface with oral, visual, audio, gestural, tactile, and spatial patterns of meaning. In the EFL context, this situation unavoidably urges changes in the goal of English language teaching to include multimodal communicative competence. In response to such challenges, multiliteracies pedagogy offers plausible solutions. In a multiliteracies classroom, students are supported through a pedagogy that provides them with ample opportunities to develop their knowledge and skills to multimodally examine diverse information sources and content, critically explore the information, and become active meaning-makers and effective communicators. This study aims at investigating the implementation of multiliteracies pedagogy in English language teaching to foster students’ multimodal communicative competence. This is a qualitative case study involving twenty students of the English language department of IAIN Curup. The data of the study are gained through observation, interviews, and students’ artefacts. The data collected from these instruments were examined qualitatively using thematic and categorical coding. The result of this study demonstrates the enactment of multiliteracies pedagogy can develop five competences of multimodal communicative competence: linguistic competence, sociocultural competence, interactional competence, discourse competence, and multimodal competence. Meanwhile the other two competences, strategic competence and formulaic competence, are somewhat hindered due to lack of exposure to authentic English language.